Avaliação da vulnerabilidade e perigo à contaminação do Aquífero Bauru, utilizando o método SI, na cidade de Primavera do Leste - MT e seu entorno - Rodrigues, Neiva Sales (2014)
Generating activities of contaminants, and improper use can cause irreversible damage to groundwater. To circumvent this problem have been adopted in various parts of the world, especially in developed countries, preventive measures, because once contaminated the aquifer, their remediation is very slow, depending on the contaminant, can last several years. The study area is the town of Primavera do Leste - MT and its surroundings, which has a population of approximately 55,000 inhabitants, and is in continuous and high growth, where the use of physical means discriminated generates a great diversity of potential sources of contamination groundwater, but with unknown impact. In assessing the vulnerability of the aquifer Bauru SI method was applied where the following parameters were used: water depth (D), recharge (R) and lithology of the aquifer (A), topography (T), the use and occupation of land (LU). The data were processed using specific software to enable the preparation of vulnerability SI map. Most of the area, showed static level between 0.5 to 3.5 meters. The lithology obtained only one band classification, average fine sandstones, whose class (Air) is 8 multiplied by 10 and by SIW (0.259) is 20.72. Most of the area was between 0 and 0.05% topographical gradient. The urban area of fluvial drainage had values between 11 and 15 classes of land cover and use, continuous and discontinuous urban area urban area had values between 15 and 19, the area of agriculture (annual crops) had the highest values of 19 to 23. The class of vulnerability ranged from negligible to moderate, according to the SI input of each parameter. The results of this research are essential to the development of a management plan for this aquifer.